Chemical Investigation and Regulation of Adipogenic Differentiation of Cultivated Moringa oleifera - Duc Dat Le; Eunbin Kim; Thinhulinh Dang; Jiseok Lee; Choon Ho Shin; Jin Woo Park; Seul-gi Lee; Jong Bae Seo; Mina Lee (MDPI AG, 2024)
Background/Objectives: Moringa oleifera is a matrix plant with the high potential to cure several diseases with its medicinal and ethnopharmacological value and nutraceutical properties. In this study, we investigated the chemical and biological properties of this plant cultivated in our local region. Methods: Leaves, roots, seeds, stem bark, and twigs of oleifera were extracted and evaluated bioactivities targeting intracellular lipid accumulation and adipocyte differentiation in 3T3-L1 preadipocytes, and UHPLC-ESI-Orbitrap-MS/MS-Based molecular networking guided isolation and dereplication of metabolites from these extracts. Results: Five extracts of different organs of M. oleifera significantly stimulated intracellular lipid accumulation and adipocyte differentiation in 3T3-L1 preadipocytes in a concentration-dependent manner. These extracts markedly increased the expression of genes related to adipogenesis and lipogenesis. Notably, these extracts promoted peroxisome proliferator-activated receptor γ (PPARγ) activity and the expression of its target genes, including phosphoenolpyruvate carboxykinase, fatty acid-binding protein 4, and perilipin-2. These adipogenic and lipogenic effects of Moringa extracts through the regulation of PPARγ activity suggests their potential efficacy in preventing or treating type 2 diabetes. Furthermore, chemical investigation revealed high contents of phytonutrients as rich sources of secondary metabolites including glycosides, flavones, fatty acids, phenolics, and other compounds. In addition, in silico studies on major components of these extracts revealed the bioavailability of major components through their binding affinity to respective proteins targeting adipocyte differentiation.